Epstein-Barr Virus Status and Subsequent Thiopurine Exposure Within a Paediatric Inflammatory Bowel Disease Population. Issue 3 (September 2021) - Harris, Rachel E.; Hegde, Vikas; Curtis, Lee; Garrick, Vikki; Gervais, Lisa; Armstrong, Lawrence; Delahunty, Caroline; Eccleston, Andrew; Al-Hourani, Ghassan; Flynn, Diana M.; Merrick, Victoria; Barclay, Andrew R.; et al.
Abstract : ABSTRACT: The use of thiopurine therapy in Epstein-Barr virus (EBV)-naïve inflammatory bowel disease (IBD) patients remains controversial due to a risk of EBV-associated complications. We evaluated EBV status and outcomes within our paediatric IBD population over an 8-year period; finding that 217 of 409 (53%) screened patients were seropositive for EBV at IBD diagnosis; that thiopurines were used in 189 of 217 (87%) seropositive and 159 of 192 (83%) seronegative patients ( P  = 0.22); and that 7 of 192 (4%) previously seronegative patients subsequently tested positive for EBV with 6 of 7 (86%) patients having concurrently recorded thiopurine use. All six patients continued thiopurine with/without a period of cessation; no EBV-associated lymphoproliferative disorders/serious complications were recorded within our cohort. A significant proportion of our patients would not receive thiopurine therapy should their use be avoided in EBV-negative patients (47%) or seronegative males (30%). The small but significant risks of thiopurine treatment must be balanced against the potential benefits of successful IBD management; further research into this is required.